1993
DOI: 10.1176/ajp.150.6.885
|View full text |Cite
|
Sign up to set email alerts
|

The Wender Utah Rating Scale: an aid in the retrospective diagnosis of childhood attention deficit hyperactivity disorder [published erratum appears in Am J Psychiatry 1993 Aug;150(8):1280]

Abstract: The WURS is sensitive in identifying childhood attention deficit hyperactivity disorder and may be useful in recognizing attention deficit hyperactivity disorder in patients with ambiguous adult psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
253
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 874 publications
(281 citation statements)
references
References 8 publications
3
253
1
1
Order By: Relevance
“…A score of ≥17 is indicative of possible adult ADHD (likely to have ADHD), while a score of ≥24 is indicative of definite ADHD (highly likely to have ADHD). Childhood ADHD was assessed by the Wender Utah Rating Scale [29], which includes 61 questions and a 5-point Likert severity scale as in the Adult ADHD Self-Report Scale. A total of ≥46 points is indicative of childhood ADHD.…”
Section: Methodsmentioning
confidence: 99%
“…A score of ≥17 is indicative of possible adult ADHD (likely to have ADHD), while a score of ≥24 is indicative of definite ADHD (highly likely to have ADHD). Childhood ADHD was assessed by the Wender Utah Rating Scale [29], which includes 61 questions and a 5-point Likert severity scale as in the Adult ADHD Self-Report Scale. A total of ≥46 points is indicative of childhood ADHD.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, all participants completed two standardized self-report rating scales designed to quantify ADHD symptoms currently and retrospectively (Rösler, Retz-Junginger, Retz, & Stieglitz, 2008). Childhood ADHD symptoms were self-rated with the short version of the Wender Utah Rating Scale (WURS-K) including 25 items on a fivepoint scale (Ward, Wender, & Reimherr, 1993). Severity of ADHD symptoms in adulthood was self-rated with the ADHD Self-Report Scale consisting of 18 items on a four-point scale corresponding to the diagnostic criteria of DSM-IV (American Psychiatric Association, 1994;Rösler et al, 2008).…”
Section: Patients With Adhdmentioning
confidence: 99%
“…This is a questionnaire developed by Lee [24] with reference to adolescent and adult Brown Attention Deficit Disorder Scale developed by Brown [25], Wender Utah rating scale (outpatient) developed by Ward et al [26] and childhood symptom case of a disease reported by Grohol. The questionnaire used a 5-point Likert scale (1~5) to rate child and adults symptoms Questions about adult symptoms comprised 34 items consisting for four factors (disorganization, emotional deficit, hyperactivity, impulsivity).…”
Section: ) Adult Attention Deficiency Questionnairementioning
confidence: 99%